2021
DOI: 10.1021/acssuschemeng.1c00493
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bio-Based Aliphatic Polyesters from Plant Oils by Efficient Molecular Catalysis: A Selected Survey from Recent Reports

Abstract: Recent development in efficient synthesis of (unsaturated) 1,ω-fatty acid diesters (and the diols), which can be used as monomers for synthesis of long chain aliphatic polyesters, especially by Pd-catalyzed isomerization alkoxycarbonylation, Ru-catalyzed olefin metathesis (self-metathesis and cross metathesis), and the tandem olefin metathesis and the ester hydrogenation from plant oils (unsaturated fatty acid esters such as methyl oleate, methyl linoleate, etc.) have been summarized. Recent development for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 147 publications
1
71
0
2
Order By: Relevance
“…One can mention, for instance, many possible routes to convert fatty-acid-based monomers into polyolefins with the most diverse pendant groups along the polymer chain via radical polymerization [ 99 ]. Nomura and Awang reviewed the many contributions available based on the synthesis of 1,ω-fatty acid diesters and diols, which can be used as monomers for the synthesis of long-chain aliphatic polyesters by numerous routes [ 100 ]. A facile route for semi-aromatic polyamides from dimethyl 9-octadecenedioate and p -xylylenediamine or diethylenetriamine was reported, leading to materials with good thermal and mechanical properties [ 101 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…One can mention, for instance, many possible routes to convert fatty-acid-based monomers into polyolefins with the most diverse pendant groups along the polymer chain via radical polymerization [ 99 ]. Nomura and Awang reviewed the many contributions available based on the synthesis of 1,ω-fatty acid diesters and diols, which can be used as monomers for the synthesis of long-chain aliphatic polyesters by numerous routes [ 100 ]. A facile route for semi-aromatic polyamides from dimethyl 9-octadecenedioate and p -xylylenediamine or diethylenetriamine was reported, leading to materials with good thermal and mechanical properties [ 101 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…The development of sustainable polymers from bio-renewable feedstocks has been an important subject not only in polymer chemistry but also in catalysis and synthetic chemistry. It has been considered that the precision polymerization technique plays a key role for the purpose, and many studies have thus been reported concerning the so-called bio-based (aliphatic) polyesters prepared from renewable resources (plant oils etc. ). Monoterpenes, consisting of two isoprene units, are promising renewable monomers due to their natural abundance and reactive conjugated 1,3-diene framework (like isoprene). Indeed, β-myrcene (myrcene) can be polymerized via radical, anionic, , or coordination (catalytic) polymerization, and especially there have been reports for copolymerization with styrene on the relevance of styrene-butadiene (SBR) or styrene-isoprene rubbers .…”
Section: Introductionmentioning
confidence: 99%
“…1 Some of them are also biobased which is an added value for in the near future fossil fuel resources may become exhausted. 2–4 Within these biobased polymers are polymacrolactones or polymacrolides (PMLs). They are polyesters with similar properties to polyethylene, and are usually obtained by ring opening polymerization (ROP) of large ring size lactones which contain 12 or more atoms in the ring and are called macrolactones (MLs).…”
Section: Introductionmentioning
confidence: 99%